Continuous improvement methodologies in manufacturing firms: A systematic review of the literature 2016-2021 (LACCEI, 2024)
The aim of this research is to determine the most commonly used continuous improvement methodologies in manufacturing companies for the identification and solution of problems in the production process that may arise. Scientific articles were used through the SCOPUS, EBSCO and SCIENCE DIRECT databases. The filtering processes were considered in order to carry out this study with articles that respond to the question posed. Similarly, some key words were used for the search, such as improvement, methodology, manufacturing, continuous improvement. Fifty articles were selected for this systematic review. The result obtained indicated that the Lean Manufacturing methodology is the most widely used by manufacturing companies in the last 6 years. Since this methodology reduces waste, costs and unproductive time, it satisfies customer needs and increases the productivity of a company, making it more competent. Similarly, the 5S tool was identified as the most used tool for improving organisation, order and cleanliness in the company. It is worth mentioning that one of the limitations presented was the free access to the documents, which prevented a more accurate search.